2019
DOI: 10.1002/mar.21208
|View full text |Cite
|
Sign up to set email alerts
|

When self‐customization backfires: The role of a maximizing mindset

Abstract: Self‐customization in online shopping contexts readily offers an abundance of options for consumers. However, the sheer amount of information can quickly become overwhelming. One way to give people the freedom to choose without overwhelming them with information is to simplify the decision process by breaking it down into a series of smaller steps. Contrary to a common assumption that simpler decisions increase choice likelihood, however, this study demonstrates that a simple by‐attribute self‐customization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
(158 reference statements)
0
5
0
2
Order By: Relevance
“…They devote more time and effort to the decision process for achieving the goal of high standards (Misuraca and Teuscher, 2013). Maximizers consider extrinsic, for instance, price information (Nardini and Sela, 2019), and intrinsic attributes, such as features, to make judgments (Brannon and Soltwisch, 2017). They try to maximize gains on all these attributes (Mao, 2016).…”
Section: Maximizers and Satisficersmentioning
confidence: 99%
See 1 more Smart Citation
“…They devote more time and effort to the decision process for achieving the goal of high standards (Misuraca and Teuscher, 2013). Maximizers consider extrinsic, for instance, price information (Nardini and Sela, 2019), and intrinsic attributes, such as features, to make judgments (Brannon and Soltwisch, 2017). They try to maximize gains on all these attributes (Mao, 2016).…”
Section: Maximizers and Satisficersmentioning
confidence: 99%
“…However, Cai et al (2016) showed a negative response to deals and discounts on purchase intentions when purchases are non-essential. Maximization influences the desire to seek better options, and individuals who satisfice do not seek products offering the best features or benefits (Nardini and Sela, 2019). Given this, we study how maximizers and satisficers differ in their intentions to search for price information.…”
Section: Introductionmentioning
confidence: 99%
“…Certes, la personnalisation permet de mieux répondre aux besoins des consommateurs (Fan et Poole, 2006 ; Tam et Ho, 2006) et de réduire leurs efforts de recherche d’information (Ansari et Mela, 2003), ce qui aboutit à une plus grande valeur perçue (Montgomery et Smith, 2009) et à des intentions d’achat (Montgomery et Smith, 2009 ; Valenzuela et al, 2009), une satisfaction (Valenzuela et al, 2009) et une fidélité (Ansari et Mela, 2003 ; Bock et al, 2016) plus élevées. Néanmoins, la personnalisation peut également accroître les préoccupations des consommateurs en matière de confidentialité (Bleier et Eisenbeiss, 2015 ; Tucker, 2012 ; 2014 ; Riegger et al, 2021 ; Zeng et al, 2021) ou déclencher chez eux un sentiment de vulnérabilité (Aguirre et al, 2015), d’inconfort (Tucker, 2012) ou de la réactance (Fitzsimons et Lehmann, 2004 ; White et al, 2008), entraînant des effets contre-productifs sur la décision d’achat (Aguirre et al, 2015 ; Bleier et Eisenbeiss, 2015 ; Nardini et Sela, 2019). Concernant plus spécifiquement l’e-personnalisation du design d’interfaces web, les résultats montrent des effets positifs sur le nombre de clics (Ansari et Mela, 2003 ; Urban et al, 2014) et l’intention d’achat (Hauser et al, 2009 ; Urban et al, 2014).…”
Section: Fondements Théoriquesunclassified
“…et une fidélité (Ansari et Mela, 2003 ;Bock et al, 2016) plus élevées. Néanmoins, la personnalisation peut également accroître les préoccupations des consommateurs en matière de confidentialité (Bleier et Eisenbeiss, 2015 ;Tucker, 2012 ;2014 ;Riegger et al, 2021 ;Zeng et al, 2021) ou déclencher chez eux un sentiment de vulnérabilité (Aguirre et al, 2015), d'inconfort (Tucker, 2012 ou de la réactance (Fitzsimons et Lehmann, 2004 ;White et al, 2008), entraînant des effets contre-productifs sur la décision d'achat (Aguirre et al, 2015 ;Bleier et Eisenbeiss, 2015 ;Nardini et Sela, 2019). Concernant plus spécifiquement l'e-personnalisation du design d'interfaces web, les résultats montrent des effets positifs sur le nombre de clics (Ansari et Mela, 2003 ;Urban et al, 2014) et l'intention d'achat (Hauser et al, 2009 ;Urban et al, 2014).…”
Section: Les Effets De L'e-personnalisationunclassified
“…Personalisation can certainly better meet consumers’ needs (Fan and Poole, 2006; Tam and Ho, 2006) and reduce their information-seeking efforts (Ansari and Mela, 2003), thus resulting in higher perceived value (Montgomery and Smith, 2009) and purchase intentions (Montgomery and Smith, 2009; Valenzuela et al, 2009), satisfaction (Valenzuela et al, 2009) and loyalty (Ansari and Mela, 2003; Bock et al, 2016). Nevertheless, personalisation may also increase consumers’ privacy concerns (Bleier and Eisenbeiss, 2015; Riegger et al, 2021; Tucker, 2012, 2014; Zeng et al, 2021) or trigger their feelings of vulnerability (Aguirre et al, 2015), discomfort (Tucker, 2012) or reactance (Fitzsimons and Lehmann, 2004; White et al, 2008), thus leading to counterproductive effects on the purchase decision (Aguirre et al, 2015; Bleier and Eisenbeiss, 2015; Nardini and Sela, 2019). Studies have shown the positive effects of web interface design e-personalisation on the number of clicks (Ansari and Mela, 2003; Urban et al, 2014) and purchase intention (Hauser et al, 2009; Urban et al, 2014).…”
Section: Theoretical Foundationsmentioning
confidence: 99%